2022
DOI: 10.1039/d2cp00020b
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced reaction mechanisms in prototypical and bathy phytochromes

Abstract: Phytochromes, found in plants, fungi, and bacteria, exploit light as a source of information to control physiological processes via photoswitching between two states of different physiological activity, i.e. a red-absorbing...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 64 publications
(181 reference statements)
0
13
0
Order By: Relevance
“…Phytochromes are typically considered to be red/far-red light sensors that interconvert between a red light-absorbing Pr state and a far-red light-absorbing Pfr state ( 26 ). However, our transcriptome data demonstrating parallel BphP1-mediated responses to red, far-red, and blue light, along with our prior demonstration of BphP1-mediated regulation of swarming motility under blue light ( 9 ), indicated that B728a BphP1, like certain other phytochromes ( 14 , 20 , 27 29 ), may be an exception to the canonical phytochrome model.…”
Section: Resultsmentioning
confidence: 99%
“…Phytochromes are typically considered to be red/far-red light sensors that interconvert between a red light-absorbing Pr state and a far-red light-absorbing Pfr state ( 26 ). However, our transcriptome data demonstrating parallel BphP1-mediated responses to red, far-red, and blue light, along with our prior demonstration of BphP1-mediated regulation of swarming motility under blue light ( 9 ), indicated that B728a BphP1, like certain other phytochromes ( 14 , 20 , 27 29 ), may be an exception to the canonical phytochrome model.…”
Section: Resultsmentioning
confidence: 99%
“…Campestris , in which the Pfr state prevails at ambient temperature [ 112 ]. Here, only the sequential H/D exchange is observed in the Pfr state, whereas the chromophore exhibits a heterogeneous structure, and its propionic side chain is deprotonated [ 110 ].…”
Section: Photo-induced Reaction Mechanism and Chromophore Structural ...mentioning
confidence: 99%
“…However, the ground state heterogeneity of Pr (also in the case of Cph1Δ2) is due to more subtle structural differences that do not affect electronic transitions to a detectable extent. Such differences include, as is the case in Pfr, the C-D and, specifically, the A-B methine bridge, as reflected by the pairwise appearance of the same mode (e.g., A-B stretching, Figure 2 ) [ 106 , 110 , 115 ]. In addition, a recent 2D IR study on Dr BphP ( Deinococcus radiodurans ) revealed heterogeneity in the hydrogen bonding environment of the ring C=O group [ 116 ].…”
Section: Photo-induced Reaction Mechanism and Chromophore Structural ...mentioning
confidence: 99%
See 2 more Smart Citations